2017
DOI: 10.1371/journal.pone.0184464
|View full text |Cite
|
Sign up to set email alerts
|

First complete female mitochondrial genome in four bivalve species genus Donax and their phylogenetic relationships within the Veneroida order

Abstract: BackgroundFour species of the genus Donax (D. semistriatus, D. trunculus, D. variegatus and D. vittatus) are common on Iberian Peninsula coasts. Nevertheless, despite their economic importance and overexploitation, scarce genetic resources are available. In this work, we newly determined the complete mitochondrial genomes of these four representatives of the family Donacidae, with the aim of contributing to unveil phylogenetic relationships within the Veneroida order, and of developing genetic markers being us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 81 publications
2
29
1
Order By: Relevance
“…Thirteen protein-coding genes, two ribosomal RNA genes, and twentytwo transfer RNA genes were annotated by MITOS (Bernt et al 2013). The 13 conserved protein-coding genes were cox (I, II, and III), nad (1, 2, 3, 4, 5, 6, and 4L), atp (6, and 8), and cob as in Venerida (Xu et al 2012;Dong et al 2016;Fernandez-Perez et al 2017;Zhong et al 2017). The sequence has been deposited in GenBank under accession number MN326303.…”
mentioning
confidence: 99%
“…Thirteen protein-coding genes, two ribosomal RNA genes, and twentytwo transfer RNA genes were annotated by MITOS (Bernt et al 2013). The 13 conserved protein-coding genes were cox (I, II, and III), nad (1, 2, 3, 4, 5, 6, and 4L), atp (6, and 8), and cob as in Venerida (Xu et al 2012;Dong et al 2016;Fernandez-Perez et al 2017;Zhong et al 2017). The sequence has been deposited in GenBank under accession number MN326303.…”
mentioning
confidence: 99%
“…The phylogenetic analyses inferred from 5S rDNA sequences provides a similar tree to that based on the 13 protein-coding genes of mitochondrial genome of the same species [ 20 ], the phylogeny based on several mitochondrial (16S, COI and Cytb) and nuclear (18S, 28S and H3) genes [ 21 ], and the phylogenetic tree derived from the mitochondrial COI gene [ 30 ]. This is in accordance with other bivalve studies where phylogenies have been successfully reconstructed by using the 5S region (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…[ 55 , 101 ]). On the other hand, ITS phylogeny displays a different topology, but in all cases D. semistriatus and D. vittatus species are grouped in the same clade when markers of different nature are used [ 20 , 21 , 30 ]. In a previous study carried out by Chow et al [ 5 ] who studied the ITS1 in several marine animals was reported that ITS1 has a limited utility for phylogenetic analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations